CCR5 Δ 32 mutation is not prevalent in Iranians with chronic HBV infection. Issue 6 (12th April 2013) - Khorramdelazad, Hossein; Hakimizadeh, Elham; Hassanshahi, Gholamhossein; Rezayati, Mohammadtaghi; Sendi, Hossein; Arababadi, Mohammad Kazemi
Abstract: CCR5 is an important chemokine receptor involved in the recruitment of specific anti‐viral immune cells (e.g., NK cells and T cytotoxic cells) to the liver. Previous studies indicated that the Δ 32 mutation in CCR5 gene led to inactivation of CCR5. Several conflicting studies have suggested that this mutation may be associated with either recovery or persistence of HBV infection. The main purpose of this study was to compare the frequency of the Δ 32 mutation within the CCR5 gene in a group of patients infected chronically with HBV with healthy individuals from South‐East of Iran. Sixty patients with chronic HBV infection as well as 300 age‐, and sex‐match healthy individuals were enrolled in this study. Gap‐PCR was applied to determine the frequency of CCR5 Δ 32 mutation in both groups. The results demonstrated that none of the patients infected with HBV carried the CCR5 Δ 32 mutation while, 3 (1%) of the healthy individuals were found to be heterozygotic for this mutation. The CCR5 Δ 32 mutation is not a prevalent mutation in either the patients infected chronically with HBV or their health counterparts in the South‐East region of Iran. This may be attributed to either different genetic settings of the investigated population or lack of any significant correlation between this mutation and HBV pathogenicity. J. Med. Virol. 85: 964–968, 2013. © 2013 Wiley Periodicals, Inc.